Research on the Countermeasures of Parental Participation in Improving Piano Education for Preschool Children - Ge, Yier (International Journal of Social Sciences and Public Administration, 2024)
This study focuses on the key role of parental involvement in children’s education in the field of music education, especially the process of children’s piano learning. Parental involvement has been shown to significantly affect a child’s academic performance, behavioral performance, social skills development, and smooth transition from kindergarten to higher grade. Especially in music education, parental support helps children build self-confidence, develop good study habits, and overcome difficulties encountered in the process of learning an instrument. Many factors, such as parents’ socioeconomic status, educational background, occupation, attitude and belief towards children’s music education, will affect their involvement in children’s music development. This study adopts a mixed method research design, combining quantitative and qualitative research methods. First of all, the basic information of parents, their participation in children’s piano learning and students’ piano learning level were collected through a questionnaire survey. SPSS software was used for frequency analysis, descriptive statistical analysis and difference analysis to explore the relationship between parents’ characteristics and participation level and the influence of participation level on students’ piano learning level. Secondly, through in-depth interviews with school administrators, qualitative data on the challenges faced by parents involved in children’s piano learning were obtained, and targeted solutions were proposed on this basis. The quantitative results show that parents’ gender, age, education level and occupation are closely related to their participation in their children’s piano learning, and parents’ participation is significantly positively correlated with students’ piano learning level. The qualitative analysis reveals the challenges encountered by parents in the process of participation, such as time and resource limitations, cognitive level and skills deficiencies, and puts forward some coping strategies, such as providing educational resources and strengthening communication and cooperation between family and school. Finally, this study emphasizes the positive role played by parents in children’s piano learning, that is, by creating a good learning environment, emotional support and strengthening family ties, it effectively promotes the development of children’s musical ability and the improvement of comprehensive quality. Therefore, it is suggested that school administrators actively advocate and promote parents to effectively participate in their children’s piano learning, and form a good mechanism of home-school cooperation and co-education to help children develop comprehensively.